La Cartografía Española en America durante el siglo XVIII: La actuación de los Ingenieros Militares - José Omar Moncada Maya (Navigator)
The numerous individuals who were mapping during the colonial era, include in their own right military engineers. This body, officially created in 1711, was a prominent contributor to the American authorities in the work of land management, through their participation in public works, works of defense, in urban works. All have left shows throughout Latin America. Together with the documentation of such works, engineers bequeathed us a very large collection of maps, which are now documentary jewels of the availability of resources offered by the new continent, in a century ruled by reason.